The Role Of Strategic Management Accounting In The Sustainable Development Goals During The Covid-19 Pandemic Yarsi Dental and Oral Hospital - Ramadhan, Yanuar; Kusdianto , Kemas Dedy; Wijaya, Santy; Wirdiansyah, Dian; Slamet, Franki (Journal Research of Social Science, Economics, and Management, 2022)
This study aims to determine the application of Sustainable Development Goals (SDGs) in the Field of Health and Education to pursue a profession in dentistry at YARSI Dental and Oral Hospital. The method used in this study is the literature review method. The data collection technique uses purposive sampling with a total of 3 (three) people with data collection used through observation, interviews and documentation, then analyzed using the data reduction stage, data presentation and drawing conclusions. The results of this study indicate that the Implementation of Sustainable Development Goals (SDGs) in the Field of Health and Education. This research can enrich the empirical analysis of the relationship between health in hospitals and educational indicators as the basis for policy making that supports the achievement of Sustainable Development Goals. In addition to the problems that until now have occurred a lot in the fields of health and education, in the future, it is hoped that it will be able to change the concept of change that is much better and directed so as to produce complete services and quality education for every hospital, especially hospitals with health and education services.